Reliability assessment of hydro-thermal composite systems by means of stochastic simulation techniques - Román Úbeda, Jaime; Allan, Ronald N. (My University, 1994)
This paper discusses the advantages of using stochastic sequential simulation techniques for the purpose of reliability assessment of hydro-thermal composite systems. These techniques can take into account virtually all contingencies inherent in the operation of the system. Also the operating policies that have an important effect on the performance of these systems can be realistically represented. A real hydro-electric system is analysed to show the effectiveness of these techniques.

This paper discusses the advantages of using stochastic sequential simulation techniques for the purpose of reliability assessment of hydro-thermal composite systems. These techniques can take into account virtually all contingencies inherent in the operation of the system. Also the operating policies that have an important effect on the performance of these systems can be realistically represented. A real hydro-electric system is analysed to show the effectiveness of these techniques.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)